Influencia del clima laboral en el desempeño de los trabajadores de la división de recursos humanos de la empresa Agroindustrial Pomalca S.A.A. - 2013 - Lescano Ramírez, Arturo (2015)
This research addresses the problem of the influence of work environment factors in the performance of the employees of the Division of Human Resources Agroindustrial Pomalca SAA in 2013, and it shows that the factors of working environment, remuneration not acceptable and hours of hard work differentially affect the performance of the employees of the Division of Human Resources. One qualitative-quantitative research was developed from a deductive and inductive perspective; analytical and ethnographic; being the object of study the factors that characterize the work environment in a sample of 70 workers from different sections and departments of the Division of Human Resources Agroindustrial Pomalca SAA The results show that the working environment is predominantly of uncertainty in the Division of Human Resources, by downsizing and minimally regulated positive because discipline and accountability; that being paid is not commensurate with their job performance; and that there is dissatisfaction with the work schedule, and is satisfied to be under law and specific administrative policies of the company, but there is good worker performance due to their strong identification with the company as an institution with a sense of belonging and the compliance with formal job functions.